2016
DOI: 10.21037/atm.2016.05.28
|View full text |Cite
|
Sign up to set email alerts
|

Engineered cell-free scaffold with two-stage delivery of miRNA-26a for bone repair

Abstract: The treatment of non-unions and bone defects is a major challenge. In these situations, autologous bone is the preferred treatment but has several serious limitations. Treatment alternatives including the use of calcium-based scaffolds alone or associated with either growth factors or stem cells have therefore been developed, or are under development, to overcome these shortcomings. Each of these are, however, associated with their own drawbacks, such as the lack of sustained/controlled delivery system for gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Meanwhile, pericytes not only promote the appearance of endothelial progenitor cells but also maintain vascular integrity to form a vascular network [ 63 ]. Studies have shown that ASCs could also participate in the formation of new micro-vessel together with endothelial cells to form a stable vascular network system [ 64 ]. Animal experiments have demonstrated that transplanted ASCs could differentiate into endothelial cells, significantly improving blood flow and capillary density in diabetic and non-diabetic animal models of lower limb ischemia [ 65 ].…”
Section: Svf Cells For Diabetic Footmentioning
confidence: 99%
“…Meanwhile, pericytes not only promote the appearance of endothelial progenitor cells but also maintain vascular integrity to form a vascular network [ 63 ]. Studies have shown that ASCs could also participate in the formation of new micro-vessel together with endothelial cells to form a stable vascular network system [ 64 ]. Animal experiments have demonstrated that transplanted ASCs could differentiate into endothelial cells, significantly improving blood flow and capillary density in diabetic and non-diabetic animal models of lower limb ischemia [ 65 ].…”
Section: Svf Cells For Diabetic Footmentioning
confidence: 99%
“…These miRNAs regulate target mRNA expression, and stimulating of miRNAs using agomiRNAs can thus modulate mRNA expression 42 . Previous research has largely explored the role of biotic factors in bone remodeling, with few studies exploring the association between TBI-related miRNAs and bone healing 30, 31, 32, 33, 43, 44. Therefore, this study identified miRNA-26a-5p in osteoblasts as a key activator of bone formation in the context of TBI.…”
Section: Discussionmentioning
confidence: 99%
“…The results of in vitro and in vivo experiments in one study have demonstrated that transfection of miR-26a significantly accelerated the osteogenic differentiation of adipose-derived stem cells in vitro and enhanced new bone formation following miR-26a transfection in vivo ( 32 ). Furthermore, the repair response to critical calvarial bone defects was demonstrated to be strengthened through positive modulation of miR-26a in angiogenic-osteogenic coupling ( 33 ). The underlying mechanism by which miR-26a positively mediates angiogenic-osteogenic coupling may be due to the fact that its high expression in newly formed bones increases vascular endothelial growth factor (VEGF) secretion.…”
Section: Discussionmentioning
confidence: 99%